The Effect Of Tapeto Patty (Tofu, Tempeh, Tomato) Consumption On Hemoglobin Level Improvement In Adolescent Girls - Nasution, Pratiwi; Damanik, Syahroni; Zuiatna, Dian (JKM (Jurnal Kebidanan Malahayati), 2025)
Background:Adolescence is a critical phase in growth and development, especially for adolescent girls who begin preparing for reproductive functions. Anemia remains a major health issue among adolescent girls in Deli Serdang Regency, with a prevalence reaching 71% in rural areas. One of the causes is low intake of nutrients, including iron and supporting vitamins. Objective : This study aims to determine the effectiveness of administering TAPETO fritters (Tofu, Tempeh, Tomato) in increasing hemoglobin (Hb) levels in adolescent girls. Methode: This study used a quantitative method with a pre-experimental one-group pretest-posttest design without a control group. Samples were selected using purposive sampling, and the intervention was carried out by providing TAPETO fritters for 21 consecutive days. Hb levels were measured five times: once before, three times during, and once after the intervention. Result : Statistical analysis showed a p-value of 0.000 < 0.05, indicating that the administration of TAPETO fritters significantly increased Hb levels in adolescent girls in Sei Baharu Village (Ha accepted and Ho rejected). Conclusion : The provision of TAPETO shows potential as a healthy and nutritious food alternative to increase Hb levels. This study is expected to produce an innovative food product for anemia management. Keywords: Adolescent Girls, Hemoglobin, Tofu, Tempeh, Tomato ABSTRAK Latar Belakang : Masa remaja merupakan fase penting dalam pertumbuhan dan perkembangan, terutama bagi remaja puteri yang mulai mempersiapkan diri untuk fungsi reproduksi. Anemia masih menjadi masalah kesehatan utama pada remaja puteri di Kabupaten Deli Serdang, dengan prevalensi mencapai 71% di daerah pedesaan. Salah satu penyebabnya adalah ren dahnya asupan zat gizi, termasuk zat besi dan vitamin pendukung. Tujuan : Penelitian ini bertujuan untuk mengetahui efektivitas pemberian perkedel TAPETO (Tahu, Tempe, Tomat) dalam meningkatkan kadar hemoglobin (Hb) pada remaja puteri. Metode : Penelitian ini menggunakan metode kuantitatif dengan desain pre-eksperimental one group pretest-posttest tanpa kelompok kontrol. Sampel dipilih menggunakan teknik purposive sampling, dan intervensi dilakukan dengan pemberian perkedel TAPETO selama 21 hari berturut-turut. Pengukuran kadar Hb dilakukan lima kali: satu kali sebelum, tiga kali selama, dan satu kali setelah intervensi. Hasil : Dari hasil uji statistic didapatkan bahwa nilai p-value 0,000 < 0,05 sehingga ada pengaruh pemberian perkedel Tahu Tempe dan Tomat (TaPeTo) terhadap Peningkatan Kadar Hb pada Remaja Puteri di Desa Sei Baharu (Ha diterima dan Ho ditolak). Kesimpulan : Pemberian TAPETO menunjukkan potensi sebagai alternatif makanan sehat dan bergizi untuk meningkatkan kadar Hb. Penelitian ini diharapkan menghasilkan produk pangan inovatif dalam penanganan anemia. Kata Kunci : Hemoglobin, Remaja Puteri, Tahu, Tempe, Tomat, ,.